2003
DOI: 10.1089/107632703322495592
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Joint: A Chimeric Construct with Bovine Chondrocytes in a Devitalized Chick Knee

Abstract: This study assessed the feasibility of a devitalized knee as a scaffold for an engineered chimeric joint. Embryonic chick knees (19 days old), devitalized by lyophilization or multiple freeze-thaw cycles, were tested as scaffolds for repopulation with bovine articular chondrocytes (bACs). bACs were seeded into porous three-dimensional collagen sponges and were cultured for 1 day before fabrication of chimeric constructs. A pair of cell-seeded sponges was inserted into the joint space to contact preshaved artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As a model for bioengineered joint, we used porous collagen sponges as a scaffold for bovine articular chondrocytes to generate articular cartilage in a chimeric construct with a devitalized chick knee. 38 Two sponges were used to resurface the femoral and tibial joint surfaces ( Figure 3). First, the construct was maintained in vitro and evaluated at intervals.…”
Section: In Vivo Fate Of Chondrocyte/collagen Spongesmentioning
confidence: 99%
“…As a model for bioengineered joint, we used porous collagen sponges as a scaffold for bovine articular chondrocytes to generate articular cartilage in a chimeric construct with a devitalized chick knee. 38 Two sponges were used to resurface the femoral and tibial joint surfaces ( Figure 3). First, the construct was maintained in vitro and evaluated at intervals.…”
Section: In Vivo Fate Of Chondrocyte/collagen Spongesmentioning
confidence: 99%
“…This structure differs from that of woven polymer lattices (Li et al 2003;Woodfield et al 2004) or collagen hydrogels. Our previous work demonstrated that these constructs meet several criteria that are desirable for tissue engineering of cartilage: they are biologically compatible (demonstrated in mice, with osteoblasts) (Gerstenfeld et al 1996); they are adherent to cartilage (Zaleske et al 2003); and they support chondrogenesis in vitro and in vivo (Warden et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…These include phalanges formed with solvent-cast synthetic polymer scaffolds in combination with periosteum and isolated chondrocytes (Isogai, et al, 1999, Landis, et al, 2005, Sedrakyan, et al, 2006), patella formed from a milled trabecular bone substrate with a molded chondrocyte-agarose layer (Hung, et al, 2003), and mandibular condyle formed from molded PEG hydrogel with stratified layers of encapsulated stem cells (Alhadlaq, et al, 2004). Whole-joint bioengineering has been attempted by apposition of engineered distal and middle phalanges with a joint capsule formed by a tenocyte-seeded PGA mesh (Isogai, et al, 1999, Landis, et al, 2005), and resurfacing devitalized chick knees with chondrocyte-seeded collagen sponges (Warden, et al, 2004, Zaleske, et al, 2003). In these whole-joint studies, anti-adhesion sheets of silicone or ePTFE were used to prevent fusion of opposing articular surfaces during in vitro or subcutaneous in vivo culture.…”
Section: Tissue Engineering Strategies For Partial and Whole Jointsmentioning
confidence: 99%